A Multi-agent approach for devices management and control in IoT environments - Cagnin, Renato L.; Guilherme, Ivan R.; Queiróz, Jonas F. P.; Antonialli, Rodrigo C. (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2014)
The Internet of Things (IoT) envisions millions of heterogeneous smart devices in an open, distributed and dynamic environment. IoT addresses the complexity involved in connecting, discovering and accessing all these devices, and also integrate and analyze the amount of data produced by them. In this paper is presented a proposal for the development of an architecture based on Multi-agent systems, Service-Oriented Architecture and Semantic Web technologies. The architecture aims to support the design and development of robust, flexible and scalable application to automate devices management and coordination in IoT based environments.